2007
DOI: 10.1007/s10164-007-0040-5
|View full text |Cite
|
Sign up to set email alerts
|

Body size and fat reserves as possible predictors of male territorial status and contest outcome in the butterfly Eumaeus toxea Godart (Lepidoptera: Lycaenidae)

Abstract: We used adults of the butterfly Eumaeus toxea for two purposes-description of male territorial behavior and investigation of whether body size and muscle fat reserves correlated with social status (resident or intruder) and the probability of winning a territorial contest in dyadic encounters. Males perched in places near cycads (Zamia furfuracea), where females lay eggs. Resident males (those with faithfulness to the same site for several days) used two types of flight of different duration, short (ca. 5 s) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 21 publications
1
20
0
2
Order By: Relevance
“…In Pararge aegeria, there is an indication that males that lose contests with other males end up being more mobile without following a true patrolling strategy (Bergman and Wiklund 2009). Success in male-male contests has been explained by a simple 'resident wins' rule (Bergman et al 2007;Davies 1978;Kemp and Wiklund 2001), but in some butterflies morphological traits such as body mass (Martinez-Lendech et al 2007;Peixoto and Benson 2008) have been shown to influence the outcome of aerial contests (though see Kemp et al 2006). In some territorial insects, the outcome of contests and male mating success may correlate with energy reserves (Marden and Rollins 1994;Otronen 1995).…”
Section: Discussionmentioning
confidence: 96%
“…In Pararge aegeria, there is an indication that males that lose contests with other males end up being more mobile without following a true patrolling strategy (Bergman and Wiklund 2009). Success in male-male contests has been explained by a simple 'resident wins' rule (Bergman et al 2007;Davies 1978;Kemp and Wiklund 2001), but in some butterflies morphological traits such as body mass (Martinez-Lendech et al 2007;Peixoto and Benson 2008) have been shown to influence the outcome of aerial contests (though see Kemp et al 2006). In some territorial insects, the outcome of contests and male mating success may correlate with energy reserves (Marden and Rollins 1994;Otronen 1995).…”
Section: Discussionmentioning
confidence: 96%
“…Two major predictors of contest outcomes are the competitive ability of individuals (resource holding potential, RHP) and the value (V) that contestants place on possession of the resource (Maynard Smith and Parker, 1976;Kokko, 2013): each of these may be affected by the nutritional status of the contestants. For example, individuals that have been well fed may be able to persist for longer during contests (RHP) due to their enhanced energy reserves (Poole, 1989;Kemp and Alcock, 2003;Martinez-Lendech et al, 2007;Briffa et al, 2013b) while individuals with depleted reserves may compete more intensely for a contested resource, due to placing a higher value (V) on its exploitation (Riechert, 1998). Further, the availability of macronutrients (protein, fats and carbohydrates) may promote dominance-related behaviours (Davidson, 1997) while other metabolites may physiologically constrain contest behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…For example, owners are larger than intruders in some butterflies (Rosenberg and Enquist 1991; Martínez-Lendech et al 2007; Peixoto and Benson 2008, 2011, 2012; Takeuchi 2011; Carvalho et al 2016). The effect of large body size on winning contests is ubiquitous in the animal kingdom (Hardy and Briffa 2013).…”
Section: Contests Over Mating Territorymentioning
confidence: 99%